The Content Of The Process For Forming The Concepts Of Tolerance In Primary Class Students - Dehkanbayev Mohammad (PT. Antis International Publisher, 2024)
In this article, the content of the concept of tolerance and the essence of the processes aimed at forming the concept of tolerance in primary classes are reflected in the article.